Turn-Taking Patterns in Online English Lessons for Young Learners: An IRF-Based Discourse Analysis - Pramudanti, Yolinda; Wasiatiningsih, Endrat (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study investigates the application of the Initiation–Response–Feedback (IRF) model and turn-taking strategies in synchronous online English classes for young learners at an English course in Indonesia. Although widely used to analyze classroom discourse, IRF’s role in online teaching, especially for young learners, remains underexplored. This study addresses that gap through a descriptive qualitative design and discourse analysis of a 50-minute Zoom session with one teacher and ten fifth-grade students. Data were transcribed and analyzed using the IRF framework to identify dominant interaction patterns and teacher strategies. Findings revealed that while IRF remained central, many exchanges occurred in fragmented forms (e.g., Initiation–Response or Initiation–Feedback), mainly due to technical issues, time limits, and lack of non-verbal cues. Response (R) moves were most frequent (44%, 74 occurrences), indicating dominant student participation. Initiation (I) accounted for 25% (43 occurrences), reflecting the teacher’s prompting role. Feedback (F) was 15% (25 occurrences), suggesting occasional teacher follow-up. Interestingly, Initiation + Feedback (I + F) comprised 16% (27 occurrences), possibly due to time or technical constraints where teacher initiation and feedback merged. Teachers managed turn-taking using name-calling, verbal cues, chat functions, and fair distribution of speaking turns. These helped sustain interaction and engagement despite platform limitations. The study underscores the need to adapt traditional interaction models for online learning and calls for more context-sensitive strategies in virtual EFL classrooms for young learners.